National rap: black youth and the musical poetical experience inside classroom - Fernandes, Ana Claudia Florindo; Martins, Raquel; Oliveira, Rosângela Paulino de (Revista do Instituto de Estudos Brasileiros, 2016)
This article is intended for thinking about the use of national rap at the school environment from its aesthetic and speech as a means to discuss with young people the history of slavery in Brazil, as well as the spread and perpetuation of racial prejudice in Brazilian society. It will englobe some experiments conducted amidst adolescents in workshops based on rap, regarding to field studies that were part of a Research Project for Public Policy in the area of Education. It will be discussed to what extent the rap, consisting of multiple languages, such as oral, music and body language, can contribute to the youth’s learning processes of African descendants, resident in the outskirts of Sao Paulo, and how it contributes to build their identities through recognition.